2013
DOI: 10.1080/09593330.2013.810294
|View full text |Cite
|
Sign up to set email alerts
|

Biological pretreatment of non-flocculated sludge augments the biogas production in the anaerobic digestion of the pretreated waste activated sludge

Abstract: High-efficiency resource recovery from municipal solid waste (MSW) has been a focus of attention. The objective of this research is to develop a bio-pretreatment process for application prior to the anaerobic digestion of MSW to improve methane productivity. Bacillus licheniformis was used for pretreating MSW (non-flocculated with 0.07% citric acid), followed by anaerobic digestion. Laboratory-scale experiments were carried out in semi-continuous bioreactors, with a total volume of 5 L and working volume of 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…The cumulative methane production data of BMP test was simulated using modified Gompertz model (GM) for control sludge and exponential model (EM) and logistic model (LM) were used for both flocculated and deflocculated samples. The modified Gompertz model was adopted following Merrylin et al, 2013. The first-order exponential model (EM) was applied for the first exponential phase of methane production (0-5 days).…”
Section: Anaerobic Batch Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The cumulative methane production data of BMP test was simulated using modified Gompertz model (GM) for control sludge and exponential model (EM) and logistic model (LM) were used for both flocculated and deflocculated samples. The modified Gompertz model was adopted following Merrylin et al, 2013. The first-order exponential model (EM) was applied for the first exponential phase of methane production (0-5 days).…”
Section: Anaerobic Batch Testmentioning
confidence: 99%
“…Studies have also revealed that divalent cations (Ca 2+ , Mg 2+ , Fe 2+ ) can bind to negative sites on EPS (such as polysaccharides and proteins) which increase the floc size and strength (Park and Novak, 2007). Also, removal of EPS destabilises the flocs and exposes the biomass to the action of external factors (Merrylin et al, 2013). Therefore, disruption of sludge biomass structure was found to be indispensable.…”
Section: Introductionmentioning
confidence: 97%
“…A biological pretreatment of WAS with the bacteria Bacillus licheniformis resulted in maximum 40 % solubilization which could further believed to enhance the biogas generation appreciably (Gopi et al 2012). A bacterial pretreatment experiment along with anaerobic digestion yielded 57 % and 53 % increment in methane content and biogas production compared with the control (Merrylin et al 2013a). A novel enzyme-secreting bacterial pretreatment was proposed in which the inoculated two mixed strains (Bacillus jerish 03 and Bacillus jerish 04) were the excellent enzyme (amylase and protease) producers.…”
Section: Reaction Mechanism Of Biological Treatmentmentioning
confidence: 95%
“…Minor alterations in ionic potency and quantity can consequently modify the morphological attributes of the sludge matrix (Merrylin et al 2013a). Extraction of these ions from the matrix will disrupt the entrapped biopolymers of the inhabitant native microbes.…”
Section: Linkage Between Eps and Hydrolasementioning
confidence: 98%
“…Pre-treatment techniques such as oxidative, mechanical, thermo-chemical, microwave, biological have been investigated by researchers on waste-activated sludge (Weemaes et al 2000;Carrère et al 2010;Nagai et al 2012;Uma Rani et al 2013;Uan et al 2013;Merrylin et al 2013;Kavitha et al 2014;Lakshmi et al 2014). Wang et al (1999) studied the effects of ultrasonic pre-treatment on the solubilization of waste-activated sludge and on methane generation.…”
Section: Need For Pre-treatment Operationsmentioning
confidence: 99%